Dynamic testing: Can a robot as tutor be of help in assessing children's potential for learning? - Resing, Wilma C.M.; Bakker, Merel; Elliott, Julian G.; Vogelaar, Bart (Journal of Computer Assisted Learning, 2019)
This study examined whether computerized dynamic testing by utilizing a robot would lead to different patterns in children's (aged 6–9 years) potential for learning and strategy use when solving series‐completion tasks. The robot, in a "Wizard of Oz" setting, provided instructions and prompts during dynamic testing. It was found that a dynamic training resulted in greater accuracy and more correctly placed pieces at the post‐test than repeated testing only. Moreover, children who were dynamically trained appeared to use more heuristic strategies at the post‐test than their peers who were not trained. In general, observations showed that children were excited to work with the robot. All in all, the study revealed that computerized dynamic testing by means of a robot has much potential in tapping into children's potential for learning and strategy use. The implications of using a robot in educational assessment were stressed further in the discussion. Lay Description: What is already known about this topic: ○Computerized dynamic testing provides information on children's potential for learning.○Computerized testing can be of help in the fine‐tuning of assessment outcomes.What this paper adds: ○Dynamic testing with a peer/table robot provides information on children's potential for learning.○Dynamic testing and training by a peer robot results in greater accuracy in solving an inductive reasoning task than repeated testing only.○Dynamically trained children show a more advanced use of analytic task solving than their peers who were not trained by a peer robot.○Dynamic testing with a peer/table robot provides detailed, step‐by‐step information regarding children's need for instruction during assessment.○Children were very eager to work with the peer/table robot. Implications for practice and/or policy: ○Detailed assessment information derived from dynamic testing may be more suitable to inform education.○Computerized testing with a peer/table provides a motivating testing environment for children who can work independently, in their own tempo, on a task.○In future, a peer/table robot may be of help in teaching/assessment situations in education.